2010
DOI: 10.1016/j.jbiomech.2010.08.005
|View full text |Cite
|
Sign up to set email alerts
|

The effect of connective tissue material uncertainties on knee joint mechanics under isolated loading conditions

Abstract: Although variability in connective tissue parameters is widely reported and recognized, systematic examination of the effect of such parametric uncertainties on predictions derived from a full anatomical joint model is lacking. As such, a sensitivity analysis was performed to consider the behavior of a three-dimensional, non-linear, finite element knee model with connective tissue material parameters that varied within a given interval. The model included the coupled mechanics of the tibio-femoral and patellof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
81
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(83 citation statements)
references
References 74 publications
2
81
0
Order By: Relevance
“…Future simulations of joint disorders (i.e., ligament injuries, cartilage defects and degenerations) justify also the use of the detailed model of the joint. It is to be emphasized that alterations in the input kinematics/kinetics, material and structural properties as well as joint flexion axis considered in this study likely influence the results the extent of which can only be quantified by proper sensitivity analyses (Dhaher et al, 2010;Moglo and Shirazi-Adl, 2005). Predicted activation levels in quadriceps and gastrocnemius muscles are in satisfactory agreement with values in the literature Lin et al, 2010;Neptune et al, 2004;Shelburne et al, 2005;Winby et al, 2009) and follow the same relative trends as measured EMG activities (Astephen, 2007;Astephen et al, 2008b).…”
Section: Discussionsupporting
confidence: 76%
“…Future simulations of joint disorders (i.e., ligament injuries, cartilage defects and degenerations) justify also the use of the detailed model of the joint. It is to be emphasized that alterations in the input kinematics/kinetics, material and structural properties as well as joint flexion axis considered in this study likely influence the results the extent of which can only be quantified by proper sensitivity analyses (Dhaher et al, 2010;Moglo and Shirazi-Adl, 2005). Predicted activation levels in quadriceps and gastrocnemius muscles are in satisfactory agreement with values in the literature Lin et al, 2010;Neptune et al, 2004;Shelburne et al, 2005;Winby et al, 2009) and follow the same relative trends as measured EMG activities (Astephen, 2007;Astephen et al, 2008b).…”
Section: Discussionsupporting
confidence: 76%
“…Specifically, we believe that our results will be useful not only for establishing diagnoses, but also for surgery in allowing for evaluation of the material properties of a patient's soft tissue in vivo using MRI. In many previous computational studies, MR images have been primarily used to generate intact FE models, followed by validation in cadavers (Haut Donahue et al, 2003;2004;Pena et al, 2006;Baldwin et al, 2009;Dhaher et al, 2010;Kwon et al, 2014). However, we hypothesize that data from evaluation of material properties in vivo using MR images will be useful for both damaged and normal knees.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the majority of previous studies refer to cadaveric or reference data in order to conduct sensitivity or probabilistic analysis (Baldwin et al, 2009;Dhaher et al, 2010). However, there are significant differences between in vivo and in vitro properties.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that under this condition, the biphasic response of cartilage can be negligible and the single-phase linear isotropic constitutive law be applicable [40,41]. Therefore, cartilage was modeled as a homogeneous, elastic, linearly isotropic material [1,2,[4][5][6][7]9,16,23,25,30,32,33,[35][36][37][38][39][42][43][44][45][46] with a modulus of 15 MPa [4,9,25,30,35,45] and a Poisson's ratio of 0.46 [31][32][33]47,48].…”
Section: Materials Propertiesmentioning
confidence: 99%
“…The menisci were therefore modeled as linearly elastic, transversely isotropic materials [1,2,4,9,10,16,25,30,[34][35][36]39,[43][44][45]52], where the modulus and Poisson's ratio were 20 MPa and 0.2, respectively, in the radial and axial directions, and 140 MPa and 0.3, respectively, in the circumferential direction [4,30,45,52]. Time dependent effects of the cartilage and menisci properties were not considered due to the quasi-static nature of the models [4,7,8,23,30,32,35,[40][41][42]48,53,54].…”
Section: Materials Propertiesmentioning
confidence: 99%